A Quasar-anchored Protocluster at z = 6.6 in the ASPIRE Survey. I. Properties of [O iii] Emitters in a 10 Mpc Overdensity Structure - Jaclyn B. Champagne; Feige Wang; Haowen Zhang; Jinyi Yang; Xiaohui Fan; Joseph F. Hennawi; Fengwu Sun; Eduardo Bañados; Sarah E. I. Bosman; Tiago Costa; Anna-Christina Eilers; Ryan Endsley; et al. (The Astrophysical Journal)
A SPectroscopic survey of bIased halos in the Reionization Era is a quasar legacy survey primarily using JWST to target a sample of 25 z  > 6 quasars with NIRCam slitless spectroscopy and imaging. The first study in this series found evidence of a strong overdensity of galaxies around J0305−3150, a luminous quasar at z = 6.61, within a single NIRCam pointing obtained in JWST Cycle 1. Here we present the first results of a JWST Cycle 2 mosaic that covers 35 arcmin ^2 with NIRCam imaging/wide-field slitless spectroscopy of the same field to investigate the spatial extent of the putative protocluster. The F356W grism data target [O iii ]+H β at 5.3 <  z  < 7 and reveal a population of 124 line emitters down to a flux limit of 1.2 × 10 ^−18 erg s ^−1 cm ^−2 . Fifty-three of these galaxies lie at 6.5 <  z  < 6.8 spanning 10 cMpc on the sky, corresponding to an overdensity within a 2500 cMpc ^3 volume of 12.5 ± 2.6, anchored by the quasar. Comparing to the [O iii ] luminosity function from the Emission line galaxies and Intergalactic Gas in the Epoch of Reionization project, we find a dearth of faint [O iii ] emitters at log( L /erg s ^−1 ) < 42.3, which we suggest is consistent with either bursty star formation causing galaxies to scatter around the grism detection limit or modest suppression from quasar feedback. While we find a strong filamentary overdensity of [O iii ] emitters consistent with a protocluster, we suggest that we could be insensitive to a population of older, more massive Lyman break galaxies with weak nebular emission on scales >​​​​​​10 cMpc.